Правові критерії визначення нерухомого майна житлом - Коваль, О. В.; Коваль, Е. В.; Koval, O. V. (Одеса : Юрид. л-ра, 2012)
The work is devoted to the study of such concepts as «housing» which is embodied in legal acts and published in scientific works, and in this work is analysed of legal criteria for determining of real estate as a «housing.» The necessity of making appropriate legislative changes.
Коваль О. В. Правові критерії визначення нерухомого майна житлом / О. В. Коваль // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 424-431.
Keywords: житло; житлові приміщення; нерухомість; об'єкти нерухомості; право на житло; жилье; жилые помещения; недвижимость; объекты недвижимости; право на жилье; housing; homes; property; real estate; the right to housing